STRATEGI ADAPTASI ETNIK ARAB DI KOTA DENPASAR - Balbed, Faris Chalid M; Suka Arjawa, I Gst Putu Bagus; Kamajaya, Gede (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2019)
ABSTRACT This research attempts to explain about the strategy that used by Arab ethnic groups to adapt with their new environment. It uses a qualitative approach and analyzed by the AGIL system theory from Talcott Parsons. The adaptation strategy that they are doing is observing and studying the Balinese people's daily life. The adaptation in aspect of social, cultural, and also understanding the local language has been well done by the Arab ethnic so they can be easily accepted by the new environment. As the time goes by, Arab ethnic can live in harmony among the Balinese ethnic and other ethnic groups around them. Hablum Minannas is a value that strongly hold by Arab ethnic in creating a good relationship between human beings. The good relations between Arab ethnic and Balinese ethnic also the other ethnicities should be sustainable so that they will always be able to run in harmony. Keywords: AGIL, Arab Ethnic, Hablum Minannas.